Queixas musculoesqueléticas em atletas de futevôlei - Cecilio, Gabriel Henrique Sampaio (2021)
Background: The practice of footvolley has been one of the fastest growing sports in Brazil, being practiced by men, women, children and the elderly. During the pandemic due to the COVID-19 virus, footvolley had an increase of 250% in practice in Brazil, taking into account the restrictions imposed by the governments of each state on various activities and sports that cause crowding and physical contact, the practice Footvolley, as it is a sport with less contact, with a reduced number of people and being performed on outdoor courts, was one of the first sports to be released during the pandemic, trying to reduce sedentary lifestyles due to isolation at home and providing better quality of life to practitioners due to psychological and physical factors.Purpose: Comparatively analyze, through an on-line questionnaire, the main musculoskeletal complaints in footvolley athlete Method: The present study was of a cross-sectional experimental nature through the application of an on-line questionnaire. Results: In total, 146 responses were collected, but only 107 met the requirements. Conclusion: The most common complaints by footvolley athletes were in the knee, hip, ankle and lumbar spine. Before the pandemic it forms larger in the knees and after the pandemic in the lumbar spine. The time of sport practice did not influence the complaints reported before and during footvolley practice. Doctors and Physiotherapists were the most sought after professionals to treat the injuries.